PENGEMBANGAN MODUL KONTEN BIOLOGI SEKOLAH UNTUK CALON GURU - Pratiwi, Ginanda Bernada; Suryawati, Evi; Suzanti, Fitra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
This study aims to determine the quality of school biology content modules for prospective teachers that are developed based on essential indicators of biological knowledge content. The research was carried out on the campus of biology education at the Faculty of Teacher Training and Education in Riau University. The research design used was the ADDIE model. This research was carried out only with the stages of analyze, design, develop. The data in this study are primary data taken using instruments in the form of validation sheets and response questionnaires. Data collected using the Likert scale 1-4, then analyzed using the average formula. Validation was carried out by 5 validators, then limited trials I and II were conducted to undergraduate biology education students. The quality of the developed modules is assessed from 5 aspects namely module format, graphics, illustrations, language, and content eligibility. Based on its validity, the quality of the developed module is feasible to be used with a validity score of all aspects with an average of 3.17 for the first submodule and 3.14 for the second sub-module with a valid category. The mean results of trials I and II on the two sub-modules in sequence were 3.40 and 3.37 with very good categories. Based on these data it can be concluded that the school biology content module is of good quality and has to be used as a source of independent learning.Key Words:Modules, Prospective Teachers, School Biology